2021
DOI: 10.3389/fcvm.2021.756057
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Intermediate-Density Lipoprotein Cholesterol Determination as a Predictor for Coronary Heart Disease Risk in Middle-Aged Men

Abstract: Background: Not only low-density lipoprotein (LDL) cholesterol but also non-high-density lipoprotein cholesterol (non-HDL-C), very low-density lipoprotein (VLDL) cholesterol (VLDL-C), and intermediate-density lipoprotein (IDL) cholesterol (IDL-C) are reported to be significant risk markers for coronary heart disease (CHD). We reported the relevance of IDL-C to Framingham risk score (F-score), but the present study addressed the relevance of IDL-C to Suita score (S-score), a risk score for coronary heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…62 Finally, data from different populations and continents, including data from Japan, South Korea and China, have reported an association between RLP-C and ASCVD. [63][64][65] In conclusion, these studies suggest that TRLs and their remnants are an integral risk factor for ASCVD; the differences in hazard ratios are likely related to differences in populations studied and use of different separation methodologies for measuring various remnant lipoproteins and their subclasses.…”
Section: Hspg;mentioning
confidence: 88%
“…62 Finally, data from different populations and continents, including data from Japan, South Korea and China, have reported an association between RLP-C and ASCVD. [63][64][65] In conclusion, these studies suggest that TRLs and their remnants are an integral risk factor for ASCVD; the differences in hazard ratios are likely related to differences in populations studied and use of different separation methodologies for measuring various remnant lipoproteins and their subclasses.…”
Section: Hspg;mentioning
confidence: 88%
“…As cholesterol is insoluble in water, its association with proteins is mandatory to allow it to flow through systemic circulation; in this regard, the LDL-C particle consists of a monolayer of phospholipid, unesterified cholesterol at the surface membrane, and fatty acid esters of cholesterol forming the hydrophobic core [20]. LDL is produced in the liver and is the result of the two-step conversion of very low-density lipoprotein (VLDL), first metabolized to intermediate-density lipoprotein (IDL) by lipoprotein lipase, which subsequently is converted to LDL by hepatic triglyceride lipase [21]. Another critical player regulating the LDL-C level is the LDL receptor.…”
Section: Low-density Lipoprotein Cholesterolmentioning
confidence: 99%
“…[24] Studies from Japan have revealed the predictive effect of RC level on the recurrence of cardiovascular events in secondary prevention, and the use of RC values can be used for better stratification of patients' cardiovascular risk. The study by Korean Huh et al showed that elevated RC levels (≥30 mg/ dL) were associated with the incidence of cardiovascular disease in adults with type 2 diabetes, independent of LDL-C. [25,26] The jackson Heart Study and the Framingham Offspring Cohort Study in the United States, representing different populations of black and white subjects, respectively, found no difference in the predictive effect of RC. [27] Additionally, 3 prominent cohort studies conducted in the United States, namely the Atherosclerosis Risk in Communities Study, the Multi-Ethnic Atherosclerosis Study, and Coronary Risk Development in Young Adults, have demonstrated that elevated levels of RC are independently associated with ASCVD among individuals without preexisting cardiovascular disease, [28] irrespective of traditional risk factors such as LDL-C, non-HDL-C, and apolipoprotein B levels.…”
Section: Epidemiologymentioning
confidence: 99%